Detecção de peptídeos de proteína hipotética de Leptospira interrogans e sua utilização na geração de anticorpos e em plataforma de diagnóstico sorológico - Santos, Jandra Pacheco dos (2019)
Pathogenic leptospiras are recognized as causative agents of leptospirosis, a re-emergent infectious disease and one of the most prevalent zoonosis worldwide, especially in tropical climates, such as Brazil. In the first chapter of this thesis, general considerations about the bacteria and the use of bioinformatics tools and IgY antibodies against leptospirosis were presented. In the second chapter, the aim was to identify in silico protein targets with potential application in the diagnosis of leptospirosis and development of vaccines, using reverse vaccinology techniques. We compared 80 strains of Leptospira interrogans using Leptospira interrogans serovar Lai as the reference genome. A total of 1096 conserved proteins absent in the hosts were identified, including 212 gene products predicted as putative surface-exposed proteins and 87 secreted proteins. We identified 37 proteins as promising candidates for the production of vaccines and as diagnostic markers. Sixteen of these proteins (43.2%) do not have a predicted family or domain by the InterProScan program. In the third chapter, we evaluated the development of IgY and IgG polyclonal antibodies from the inoculation of chickens and rabbits, respectively, with epitopes chemically synthesized and predicted from the hypothetical protein (AAN50190.1) of Leptospira interrogans. Three B cell epitopes (P127, P128 and P129) were selected. A total of 8.05 ± 0.55 mg / mL of total IgY antibodies extracted from the yolk were obtained. In the standardization of enzyme-linked immunosorbent assay (ELISA), the peptide with the highest humoral response induction was P127. The maximum titre obtained for yolk and serum IgY was 1,600 and 200, respectively, and for rabbits 800. In the indirect immunofluorescence (IFT) reaction, IgY antibodies (1:50) recognized leptospiras. In this study, the synthetic peptides of L. interrogans induced the production of specific IgY antibodies and were shown to be promising for use in ELISA and IFT platforms for the study of leptospirosis. In the fourth chapter, the aim was the standardization of an ELISA platform using synthetic peptides (ELISApeptide) of L. interrogans (P127, P128 and P129) for the diagnosis of bovine leptospirosis. P127 showed the best reactivity during the optimization and was selected for the standardization tests using bovine serum panels from two herds (RB1, n = 80, RB2, n = 100). The relative sensitivity and specificity (ELISA versus MAT) for RB1 and RB2 were 85% - 93% and 78% - 80%, respectively. The Kappa index for RB1 and RB2 were 78% (good) and 58% (regular), respectively. In this study, the synthetic peptides of the hypothetical protein of L. interrogans were recognized by serum IgG antibodies from bovines naturally exposed to the bacterium. The epitopes of L. interrogans hypothetical proteins predicted by immunoinformatic are promising for the development of specific biologicals, ELISA and IFT platforms, and are recognized by natural infection antibodies.